IMPLEMENTASI MODEL PEMBELAJARAN INDEX CARD MATCHDALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARANPENDIDIKAN AGAMA ISLAM PESERTA DIDIK KELASVIII A SMP NEGERI 1 KOLAKA - ERNA; M Zakariah; Andi Nurul Aulia (Jurnal Teknologi Pendidikan Madrasah, 2025)
Lack of attention of students during learning so that there are still students whose learning outcomes have not reached the criteria for achieving learning objectives. Therefore, it is necessary for teachers to find the best solutions to existing problems so that students are able to have problem solving abilities in learning that are more critical, independent and enjoyable. . So the solution to overcome existing problems is to change the teacher's learning model by implementing a new learning model in a research entitled "Implementation of the Index Card Match Learning Model in Improving Learning Outcomes for Class VIII A Students at SMP Negeri 1 Kolaka".The formulation of the problem in this research is how to use the Index Card Match Learning Model in improving student learning outcomes in the Islamic Religious Education subject class VIII A of SMP Negeri 1 Kolaka and what are the student learning outcomes in the Islamic Religious Education subject through the Index Card Match learning model class VIII A of SMP Negeri 1 Kolaka? The aim of the research is to find out how the Index Card Match Learning Model is used in improving student learning outcomes in the Islamic Religious Education subject class VIII A of SMP Negeri 1 Kolaka and to find out what student learning outcomes are in the Islamic Religious Education subject through the Index Card Match learning model class VIII A of SMP Negeri 1 Kolaka. The research methods used include the type of research in the form of classroom action research (PTK); The research subjects were students in class VIII A at SMP Negeri 1 Kolaka sub-district Kolaka Regency Kolaka. The research procedures carried out included four stages, namely action planning, action implementation, observation and reflection; The research instrument is in the form of teacher and student observation sheets as well as technical learning outcomes test sheets, observation data analysis and student learning outcomes test analysis. The results of the research show that by using the Index Card Match learning model, student learning outcomes have increased in the pre-cycle test, students' achievement of classical learning completeness by 52%, in the implementation of actions in cycle I, 73% and in cycle II, achievement of learning completeness by 100%.